An intelligent transmission method for multimodal data streams in telemedicine based on multi-path transmission over wide area network - Tong, Yue; Li, Lyu; Li, Siyuan; Wang, Lei; Ma, Jun; Lyu, Ting; He, Kunlun (Frontiers in Communications and Networks, 2025)
This paper presents an intelligent multipath transmission method for multimodal data streams over wide area networks (WANs), addressing challenges such as network delay and packet loss in telemedicine scenarios. Utilizing a content-aware approach, the proposed method assigns transmission priorities to different types of data and selects optimal paths via an intelligent routing algorithm based on real-time network conditions. The system incorporates mechanisms for dynamic path switching, load balancing, and fault tolerance. Experimental results demonstrate that under conditions of link interruption and insufficient bandwidth, the proposed method achieves significantly better transmission quality compared to traditional approaches. For instance, in scenarios with 40% packet loss, the average network delay for high-priority data was reduced to 141.8 ms, compared to 297.2 ms and 318.2 ms for conventional methods. Additionally, with bandwidth reduced to 2 Mbps, the high-priority data stream’s average bit rate and frame rate were maintained at 2.67 Mbps and 29 FPS, respectively, ensuring reliable performance during critical operations.